2020
DOI: 10.21511/im.16(2).2020.09
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of omni-channel banking and preview of upcoming developments in Germany

Abstract: Banks have not come to rest since the 2008 banking crisis and have been struggling for their future ever since. In addition to serious market distortions, there are increasingly digital challenges and investments in the banks’ platforms to remain competitive and continue to meet customer requirements. Other industries are showing the banks how to do it and investing heavily in the networking of distribution channels to form an omni-channel system, as this is where all interfaces converge. The banking industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…After the financial and economic crises that erupted in 2007-2009, it was observed that the financial sector in Europe was still vulnerable and did not function reliably. After the 2008 banking crisis, banks have been struggling for their future (Menrad, 2020). Obviously, in the monetary union such as the Eurozone, problems caused by close links between public sector finance and the banking sector can easily transcend national borders and cause financial distress in all member states.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…After the financial and economic crises that erupted in 2007-2009, it was observed that the financial sector in Europe was still vulnerable and did not function reliably. After the 2008 banking crisis, banks have been struggling for their future (Menrad, 2020). Obviously, in the monetary union such as the Eurozone, problems caused by close links between public sector finance and the banking sector can easily transcend national borders and cause financial distress in all member states.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…To analyse the positioning of banks for the future, Menrad (2020) wrote in his study about the evaluation of omni-channel management in banking. It found that banks are already thinking hard about introducing omni-channel concepts in banking.…”
Section: Limits and Directions For Further Researchmentioning
confidence: 99%
“…Banks are also lagging behind other industries in this context. Omni-channel management in German bank distribution will change significantly (Menrad, 2020). Existing omni-channel concepts of savings banks and cooperative banks could also be analysed in the context of further research using concrete key figures.…”
Section: Limits and Directions For Further Researchmentioning
confidence: 99%
“…Internet banking, mobile banking, telephone banking) (Sousa & Voss, 2004). Digitalisation enables banks to network their distribution channels and customer touchpoints holistically in order to create added value for bank customers (Menrad, 2020). In this respect, there is no fundamental difference between the different sectors, although in banking, compared to retail and wholesale where the decline in branch numbers occurred earlier, bank branches continued to be frequented by customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Low branch utilization was also caused by a changed pricing policy of the banks. Advisory-intensive products were distributed through the branches, standardized products through other channels (Menrad, 2020). As a result, business activities gradually shifted and customers were encouraged to access the digital channels.…”
Section: Bank Branches In the European Union 2007-2019mentioning
confidence: 99%